Acceptance and Commitment Therapy for Muscle Disease (ACTMus): protocol for a two-arm randomised controlled trial of a brief guided self-help ACT programme for improving quality of life in people with muscle diseases. Issue 10 (3rd October 2018) - Rose, Michael R; Norton, Sam; Vari, Chiara; Edwards, Victoria; McCracken, Lance; Graham, Christopher D; Radunovic, Aleksandar; Chalder, Trudie
Abstract : Introduction: In adults, muscle disease (MD) is often a chronic long-term condition with no definitive cure. It causes wasting and weakness of the muscles resulting in a progressive decline in mobility, alongside other symptoms, and is typically associated with reduced quality of life (QoL). Previous research suggests that a psychological intervention, and in particular Acceptance and Commitment Therapy (ACT), may help improve QoL in MD. ACT is a newer type of cognitive behavioural treatment that aims to improve QoL by virtue of improvement in a process called psychological flexibility. The primary aim of this randomised controlled trial (RCT) is to evaluate the efficacy of a guided self-help ACT programme for improving QoL in people with MD. Main secondary outcomes are mood, symptom impact, work and social adjustment and function at 9-week follow-up. Methods and analysis: Acceptance and Commitment Therapy for Muscle Disease is an assessor-blind, multicentre, two-armed, parallel-group RCT to assess the efficacy of ACT plus standard medical care (SMC) compared with SMC alone. Individuals with a diagnosis of one of four specific MDs, with a duration of at least 6 months and with mild to moderate anxiety or depression (Hospital Anxiety and Depression Scale score ≥8) will be recruited from UK-based MD clinics and MD patient support organisations. Participants will be randomised to either ACT plus SMC or SMC alone by an independent randomisation service. Participants will be followed up at 3, 6 and 9 weeks. Analysis will be intention to treat, conducted by the trial statistician who will be blinded to treatment allocation. Ethics and dissemination: The study has received full ethical approval. Study results will be disseminated via peer-reviewed publications, conference presentations and journal articles. Data obtained from the trial will enable clinicians and health service providers to make informed decisions regarding the efficacy of ACT for improving QoL for patients with MD. Trial registration number: NCT02810028 . Protocol version: V.11 (4 April 2017).